Corporate governance and the extent of directors' remuneration disclosure - Ku Ismail, Ku Nor Izah; Wan Hussin, Wan Nordin; Kamardin, Hasnah; Che Adam, Noriah; Mat Zin, Rosliza; Salim, Basariah; Ahmad Zaluki, Nurwati Ashikkin; Md Yusof, Mohd 'Atef; Aripin, Norhani; Abu Bakar, Robiah; Elham, Faisol; Abdullah, Zaimah (Universiti Utara Malaysia, 2012)
This study aims to investigate the extent of Malaysian directors’ remuneration disclosure in the annual reports. In addition, this research seeks to examine the relationship between corporate governance structure and the disclosure practices of directors’ remuneration. We measure the extent of directors’ remuneration disclosure by the following four measures – the disclosure of individual pay for each director, band of pay, linkage to performance, and components of pay. Drawing on agency theory, we expect that the extent of directors’ remuneration disclosure is positively associated with the independence of boards of directors, audit committees and remuneration committees. In addition, we expect an inverse relationship between directors’ remuneration disclosure and ownership structure. The annual reports of 376 companies listed on Bursa Malaysia are randomly selected and analyzed.The results reveal that most of the sampled firms communicate information about the directors’ pay in bands of RM50,000, together with the narration of linkages between the directors’ pay and performance in their annual reports.Not many companies disclose information about individual directors’ pay, or separately disclose the salary and bonus components.In addition, the regression results suggest that the independent of board of director and remuneration committee are associated with disclosure of directors’ pay bands.Bigger firms are more likely to communicate individual director’s pay, and disclose salary and bonus components separately in their annual reports.The findings have important implication in understanding the disclosure practices of companies in relation to the directors’ remuneration.